Improvement in Retinal Capillary Rarefaction After Valsartan Treatment in Hypertensive Patients - Jumar, Agnes; Harazny, Joanna M.; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Schmieder, Roland (Journal of Clinical Hypertension, 2016)
Decreased capillary density influences vascular resistance and perfusion. The authors aimed to investigate the influence of the renin-angiotensin receptor blocker valsartan on retinal capillary rarefaction in hypertensive patients. Retinal vascular parameters were measured noninvasively and in vivo by scanning laser Doppler flowmetry before and after 4 weeks of treatment with valsartan in 95 patients with hypertension stage 1 or 2 and compared with 55 healthy individuals. Retinal capillary rarefaction was determined with the parameters intercapillary distance (ICD) and capillary area (CapA). In hypertensive patients, ICD decreased (23.4±5.5 ?m vs 21.5±5.6 ?m, P<.001) and CapA increased (1564±621 vs 1776±795, P=.001) after valsartan treatment compared with baseline. Compared with healthy normotensive controls (ICD 20.2±4.2 ?m, CapA 1821±652), untreated hypertensive patients showed greater ICD (P<.001) and smaller CapA (P=.019), whereas treated hypertensive patients showed no difference in ICD (P=.126) and CapA (P=.728). Therapy with valsartan for 4 weeks diminished capillary rarefaction in hypertensive patients.
EVALuna2:3866